An exploration of franchising in Africa - (:unkn) unknown (My University, 2017)
With promising projected growth in terms of economic indicators and population, African countries have become attractive to both non-African and African franchisors. This chapter’s objective is to initiate research on franchising in Africa by looking at concrete examples of international and African franchise businesses in various African countries with a special focus on South Africa and Egypt. This chapter adds to the literature on franchising in emerging countries and, more specifically, to the limited stream dealing with franchising in Africa. It also contributes to the practice by providing an overview of the franchise business in South Africa and Egypt and by highlighting the opportunities and challenges for both international and African franchisors.
Keywords: African Research